Defence versus defence: Are crucian carp trading off immune function against predator‐induced morphology?. Issue 10 (8th July 2019) - Vinterstare, Jerker; Hegemann, Arne; Nilsson, Per. Anders; Hulthén, Kaj; Brönmark, Christer
Abstract: Numerous species adopt inducible defence strategies; that is, they have phenotypically plastic traits that decrease the risk of capture and consumption by potential predators. The benefits of expressing alternative phenotypes in high‐ vs. low‐risk environments are well documented. However, inducible anti‐predator traits are also expected to incur costs, as they are not expressed when predators are absent, yet empirical evidence of such costs remains scarce. Virtually, all animals in nature are simultaneously under strong selection to evade both capture by predators and infection by parasites or pathogens and, hence, display a diverse arsenal of defences to combat these threats, raising the possibility of trade‐offs between defences. A classic example of a predator‐induced morphological defence is the deep‐bodied shape of crucian carp that reduces risk of predation from gape‐size‐limited predators. The goal of this study was to examine whether predator exposure affects also immune function in crucian carp, and whether the degree of expressed morphological defence is traded off against immune function in individuals. Following exposure to manipulations of perceived risk (predator presence/absence) in a long‐term experiment (8 months), key aspects of innate immune function and individual differences in the expression of inducible morphological defence were quantified. Predator‐exposed individuals showed lower haptoglobin levels and complement activity, but higher natural antibody titres than fish from predator‐free conditions. When experimentally challenged with a mimicked bacterial infection (LPS injection), fish reared in the presence of a natural predator showed a weaker immune response. Moreover, among predator‐exposed individuals, the magnitude of morphological defence expression correlated with both baseline immune function and the ability to mount an immune response. However, these relationships were not consistently supportive of a general trade‐off among defences. Our results suggest that fish exposed to predators on average reduce investment in immune function, and, further, the observed relationships among defences in predator‐exposed individuals can best be explained from individual fitness and pace‐of‐life perspectives. Abstract : The authors examined whether predator presence and the degree of an inducible morphological defence alter innate immune function in prey. Predation risk reduced investment into immune function, and defences were highly correlated among predator‐exposed crucian carp. The authors argue that these findings can best be explained from individual fitness and pace‐of‐life perspectives.